Identifikasi dan Prevalensi Cacing pada Saluran Pencernaan Ikan Gurami (Osphronemus gouramy) di Desa Ngrajek Magelang Jawa Tengah [Identification And Prevalence Of Worms On Gouramy Gastrointestinal (Osphronemus gouramy) In Ngrajek Village Magelang Central Java] - Gunanti Mahasri; Riza Aryani; Kismiyati Kismiyati (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Gouramy is one of the consumption of freshwater fish that have high economic value. Gouramy is a freshwater fish that have long been known and cultivated. Gouramy has many features including less demanding requirements for life, except that carp have slow growth. In maintenance appeared several constraints, such as illness. One possible cause is parasites. This research is aimed to know both the kind and the prevalence of gouramy gastrointestinal worms in Ngrajek Village Magelang Central Java. This research used survey methods through sampling at the site directly. Sample was taken once for 48 gouramy from four sites by using with fish size 10-15 cm. The main parameters of the research is the kind and prevalence degree of worms were found in the gastrointestinal of gouramy in the Ngrajek Magelang Central Java, while the supporting parameters in this research are water quality such as pH, temperature, dissolved oxygen (DO), and ammonia. The result of this research showed that from 48 gouramy from four sites, there was four samples that positively infected by gastrointestinal worms. The prevalence rate of gouramy infected with worms in the gastrointestinal for A location is 12.5%, for B location is 13.3%, for C location is 0%, and for D location is 10%. Worms prevalence rates are found in the gastrointestinal consists of Echinorhynchus 6.25%, Neoechinorhynchus 2.08% and Pallisentis 2.08%. Overall prevalence of gouramy infected with worms in the gastrointestinal in Ngrajek Village Magelang Central Java is 8.33%.